Congenital myasthenic syndrome: Correlation between clinical features and molecular diagnosis. (17th November 2021) - Estephan, Eduardo P.; Zambon, Antonio A.; Thompson, Rachel; Polavarapu, Kiran; Jomaa, Danny; Töpf, Ana; Helito, Paulo V. P.; Heise, Carlos O.; Moreno, Cristiane A. M.; Silva, André M. S.; Kouyoumdjian, Joao A.; Morita, Maria da Penha; et al.
Abstract: Objectives: To present phenotype features of a large cohort of congenital myasthenic syndromes (CMS) and correlate them with their molecular diagnosis. Methods: Suspected CMS patients were divided into three groups: group A (limb, bulbar or axial weakness, with or without ocular impairment, and all the following: clinical fatigability, electrophysiology compatible with neuromuscular junction involvement and anticholinesterase agents response), group B (limb, bulbar or axial weakness, with or without ocular impairment, and at least one of additional characteristics noted in group A) and group C (pure ocular syndrome). Individual clinical findings and the clinical groups were compared between the group with a confirmed molecular diagnosis of CMS and the group without molecular diagnosis or with a non‐CMS molecular diagnosis. Results: Seventy‐nine patients (68 families) were included in the cohort: 48 in group A, 23 in group B and 8 in group C. Fifty‐one were considered confirmed CMS (30 CHRNE, 5 RAPSN, 4 COL13A1, 3 DOK7, 3 COLQ, 2 GFPT1, 1 CHAT, 1 SCN4A, 1 GMPPB, 1 CHRNA1 ), 7 probable CMS, 5 non‐CMS and 16 unsolved. The chance of a confirmed molecular diagnosis of CMS was significantly higher for group A and lower for group C. Some individual clinical features, alterations on biopsy and electrophysiology enhanced specificity for CMS. Muscle imaging showed at least mild alterations in the majority of confirmed cases, with preferential involvement of soleus, especially in CHRNE CMS. Conclusions: Stricter clinical criteria increase the chance of confirming a CMS diagnosis, but may lose sensitivity, especially for some specific genes. Abstract : Seventy‐nine patients with clinically suspected congenital myasthenic syndrome (CMS) underwent high‐throughput molecular screening. Fluctuating symptoms not restricted to ocular muscles and myasthenic electrophysiological alterations were the phenotypic characteristics with the greatest chance of reaching the molecular diagnosis of CMS. Interestingly, muscle alterations, on biopsy and on resonance imaging, were prevalent in confirmed cases.